Personal and Institutional Factors Affecting the Teaching Performance of Public Secondary Science Teachers - Macacuna, Johaira (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the personal professional capacity and institutional factors affecting the teaching performance of public secondary science teachers in the Division of Lanao del Sur I-B during School Year 2025–2026. Anchored in Bandura’s Social Cognitive Theory and Bronfenbrenner’s Ecological Systems Theory, it employed a descriptive-correlational design involving 50 science teachers from 26 public secondary schools selected through total enumeration. Data were gathered using a researcher-developed, expert-validated, and pilot-tested questionnaire covering teaching self-efficacy, instructional competence, professional development, administrative and leadership support, instructional and laboratory resources, workload, and PPST-based teaching performance. Frequency, percentage, mean, standard deviation, independent-samples t-test, one-way analysis of variance, Pearson correlation, and multiple regression were used to analyze the data. Results showed very high teaching self-efficacy, instructional competence, and teaching performance, with classroom management receiving the highest performance rating. Institutional factors and professional development were rated high, while the replacement of damaged or outdated science materials received the weakest assessment. Teaching self-efficacy differed significantly according to years of experience, perceptions of institutional factors differed according to educational attainment, and instructional delivery and learner engagement differed according to age. Personal professional capacity and institutional factors were significantly and positively related to teaching performance, with correlation coefficients ranging from r = .40 to .76, p < .05. Personal professional capacity had a strong positive relationship with teaching performance, while institutional factors had a moderate positive relationship. The regression model was statistically significant, F = 38.96, p < .001, and the predictors collectively explained 62% of the variance in teaching performance. Personal professional capacity contributed more strongly to the prediction of teaching performance than institutional factors, B = .90, p < .001. The study recommends sustained science-specific professional development, strengthened administrative support, improved workload management, and increased provision and maintenance of instructional and laboratory resources through the proposed Science Teachers’ Professional Capacity and Institutional Support Enhancement Program. The study supports SDG 4 on Quality Education, SDG 9 on Industry, Innovation and Infrastructure, and SDG 10 on Reduced Inequalities. Its sustainability impact lies in strengthening long-term instructional quality, institutional capacity, equitable resource allocation, and responsive science education in disadvantaged communities.